Genome-wide identification, phylogenetic analysis, and expression profiles of trihelix transcription factor family genes in quinoa (Chenopodium quinoa Willd.) under abiotic stress conditions - Kuiyin Li; Yue Fan; Guangyi Zhou; Xiaojuan Liu; Songshu Chen; Xiangcai Chang; Wenqiang Wu; Lili Duan; Maoxing Yao; Rui Wang; Zili Wang; Mingfang Yang; et al. (BMC Genomics, 2022)
Abstract Background The trihelix family of transcription factors plays essential roles in the growth, development, and abiotic stress response of plants. Although several studies have been performed on the trihelix gene family in several dicots and monocots, this gene family is yet to be studied in Chenopodium quinoa (quinoa). Results In this study, 47 C. quinoa trihelix (CqTH) genes were in the quinoa genome. Phylogenetic analysis of the CqTH and trihelix genes from Arabidopsis thaliana and Beta vulgaris revealed that the genes were clustered into five subfamilies: SIP1, GTγ, GT1, GT2, and SH4. Additionally, synteny analysis revealed that the CqTH genes were located on 17 chromosomes, with the exception of chromosomes 8 and 11, and 23 pairs of segmental duplication genes were detected. Furthermore, expression patterns of 10 CqTH genes in different plant tissues and at different developmental stages under abiotic stress and phytohormone treatment were examined. Among the 10 genes, CqTH02, CqTH25, CqTH18, CqTH19, CqTH25, CqTH31, and CqTH36, were highly expressed in unripe achenes 21 d after flowering and in mature achenes compared with other plant tissues. Notably, the 10 CqTH genes were upregulated in UV-treated leaves, whereas CqTH36 was consistently upregulated in the leaves under all abiotic stress conditions. Conclusions The findings of this study suggest that gene duplication could be a major driver of trihelix gene evolution in quinoa. These findings could serve as a basis for future studies on the roles of CqTH transcription factors and present potential genetic markers for breeding stress-resistant and high-yielding quinoa varieties.